2011
DOI: 10.3390/su3070984
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Innovation and Sustainability in Small Handicraft Businesses in Mexico

Abstract: Abstract:In this study, the relationship between environmental innovation and sustainability is analyzed in 168 handicraft businesses in the Mexican states of Oaxaca, Puebla, and Tlaxcala. The results show a direct, positive relationship between environmental innovation and sustainability in three dimensions: economic, social, and environmental. In terms of determination, the variables that best explain sustainability are: organization type, product innovation, and process innovation. The age of the handicraft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 23 publications
3
49
0
2
Order By: Relevance
“…Researchers (Lopez-Valeiras et al, 2015;Kobayashi et al, 2011;Sánchez-Medina et al, 2011) and policymakers (e.g. OECD 2010) are becoming more and more interested in sustainable innovation and its link with organizational performance.…”
Section: Sustainable Innovation and Organizational Performancementioning
confidence: 99%
“…Researchers (Lopez-Valeiras et al, 2015;Kobayashi et al, 2011;Sánchez-Medina et al, 2011) and policymakers (e.g. OECD 2010) are becoming more and more interested in sustainable innovation and its link with organizational performance.…”
Section: Sustainable Innovation and Organizational Performancementioning
confidence: 99%
“…Researchers [1,2] and policymakers [3,4] are becoming more and more interested in sustainable innovation and its connection with organizational performance. Moreover, stakeholders are becoming increasingly aware of sustainability in international business activities.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to a resistance to changing existing routines and the cost of required changes in technology, which is not recoverable in the short term. Sánchez‐Medina, Corbett and Toledo‐López (), however, suggest that older businesses may show a greater interest in environmental issues as a result of their acquired experience and prestige. Mohan‐Neill () found that older firms are also more likely to possess the necessary infrastructure to manage environmental issues at a lower cost.…”
Section: Theoretical Frameworkmentioning
confidence: 99%